2003
DOI: 10.4319/lom.2003.1.39
|View full text |Cite
|
Sign up to set email alerts
|

A fluviarium with controlled water quality for preference—avoidance experiments with fish and invertebrates

Abstract: The effect of environmental variables on movement of aquatic organisms can be examined using preferenceavoidance behaviors. Fluviariums have been used to examine such preference-avoidance behaviors in fish, including choices associated with various water quality variables. The sharp gradient in fluviariums provides aquatic organisms with a choice of (usually) two water qualities, sharply demarcated at a relatively narrow boundary zone. A detailed description of a recently constructed and up-dated fluviarium, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 24 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…The effect of environmental variables on movement of aquatic organisms can be examined using preference and avoidance behaviors (KROON & HOUSEFIELD, 2003). Water pH is usually regulated by the carbonate -bicarbonate system, generally remaining between 6.0 and 8.0.…”
Section: O Objetivo Deste Estudo Foi Verificar O Ph Preferencial De Jmentioning
confidence: 99%
“…The effect of environmental variables on movement of aquatic organisms can be examined using preference and avoidance behaviors (KROON & HOUSEFIELD, 2003). Water pH is usually regulated by the carbonate -bicarbonate system, generally remaining between 6.0 and 8.0.…”
Section: O Objetivo Deste Estudo Foi Verificar O Ph Preferencial De Jmentioning
confidence: 99%
“…This design is similar to the one used by Kroon and Housefield [17] and, though rectangular in shape, is classified as a type of Y-maze because of its single entry with two separate arms and independent water flows. The four, two-choice Y-maze tanks were constructed using white opaque acrylic plastic.…”
Section: Diazinon Preparation Dosing and Measurementmentioning
confidence: 99%
“…Two-choice (Y-maze) fluviariums and olfactory scents Fluviariums have been used for decades to test preferenceavoidance behavior in fish [17] and are typically modified versions of the design used by Höglund [20]. This design is similar to the one used by Kroon and Housefield [17] and, though rectangular in shape, is classified as a type of Y-maze because of its single entry with two separate arms and independent water flows.…”
Section: Diazinon Preparation Dosing and Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…The usual pH range for fish growth is 6.0 to 9.0; lower pH can occur due to the presence of acidic cations, humic and fulvic acids, and more alkaline pH can be due to high levels of carbonate and other ions (Parra & Baldisserotto, 2007). Water quality may elicit a preference or avoidance response in fish (Kroon & Housefield, 2003), and several studies have demonstrated that fish preferred a specific pH (Jones et al, 1985;Nakamura, 1986;Peterson et al 1989;Åtland & Barlaup 1996;Åtland, 1998;Ikuta et al, 2003;Kroon & Housefield, 2003, Kroon, 2005, Scott et al, 2005, Riffel et al, 2012.…”
Section: Introductionmentioning
confidence: 99%